Transcriptome profiling of immune responses to cardiomyopathy syndrome (CMS) in Atlantic salmon - Alarcon Marta; Nilsen Pål; Krasnov Aleksei; Timmerhaus Gerrit; Afanasyev Sergey; Rode Marit; Takle Harald; Jørgensen Sven (BMC Genomics, 2011)
Abstract Background Cardiomyopathy syndrome (CMS) is a disease associated with severe myocarditis primarily in adult farmed Atlantic salmon ( Salmo salar L.), caused by a double-stranded RNA virus named piscine myocarditis virus (PMCV) with structural similarities to the Totiviridae family. Here we present the first characterisation of host immune responses to CMS assessed by microarray transcriptome profiling. Results Unvaccinated farmed Atlantic salmon post-smolts were infected by intraperitoneal injection of PMCV and developed cardiac pathology consistent with CMS. From analysis of heart samples at several time points and different tissues at early and clinical stages by oligonucleotide microarrays (SIQ2.0 chip), six gene sets representing a broad range of immune responses were identified, showing significant temporal and spatial regulation. Histopathological examination of cardiac tissue showed myocardial lesions from 6 weeks post infection (wpi) that peaked at 8-9 wpi and was followed by a recovery. Viral RNA was detected in all organs from 4 wpi suggesting a broad tissue tropism. High correlation between viral load and cardiac histopathology score suggested that cytopathic effect of infection was a major determinant of the myocardial changes. Strong and systemic induction of antiviral and IFN-dependent genes from 2 wpi that levelled off during infection, was followed by a biphasic activation of pathways for B cells and MHC antigen presentation, both peaking at clinical pathology. This was preceded by a distinct cardiac activation of complement at 6 wpi, suggesting a complement-dependent activation of humoral Ab-responses. Peak of cardiac pathology and viral load coincided with cardiac-specific upregulation of T cell response genes and splenic induction of complement genes. Preceding the reduction in viral load and pathology, these responses were probably important for viral clearance and recovery. Conclusions By comparative analysis of gene expression, histology and viral load, the temporal and spatial ...